Abusive supervision in government - Caillier, James Gerard 1969- (Lexington Books, 2021)
"The author uses a mixed-method approach to contend that organizational and subordinate factors either increase or decrease the presence of abusive supervision and that abusive supervision adversely affects government employees. A mixed-method approach is also used to argue that problems concerning the abusive supervision reporting process exists"--Provided by publisher.